Why suffering? : finding meaning and comfort when life doesn't make sense - Zacharias, Ravi; Vitale, Vince (Chennai, India RZIM Educational Trust, 2014)
"Why would a loving and powerful God allow so much pain and suffering? In WHY SUFFERING? Ravi Zacharias and Vince Vitale carefully walk you through a variety of responses that considered together provide a clear, comprehensive, and convincing answer. Responses like: Where there is the possibility of love, there has to be the reality of freedom, and therefore the possibility of pain. Wishing God had made a different world is to wish yourself out of existence. The cross is the key to a compelling and rational explanation for trusting in God in the face of suffering. In comparison with other world religions, the Christian response is highly distinctive. The reality of evil only makes sense in light of the reality of divine goodness. Relational knowledge about God takes the argument beyond reason to the presence of God amidst suffering. God's decision to allow temporal suffering is understandable when viewed from an eternal perspective. Divine goodness shows how to conquer not in spite of, but even through suffering. Here is a book written with great respect for the complexity of the issue, recognizing that some who read it will be in the trenches of deep suffering themselves and others questioning the very existence of a loving God. WHY SUFFERING? provides an answer to the problem of pain and suffering with emotional sensitivity and intellectual integrity"--
Includes bibliographical references.
Keywords: Suffering -- Religious aspects -- Christianity; Pain -- Religious aspects -- Christianity; RELIGION / Christian Theology / Apologetics; RELIGION / Christian Life / Death, Grief, Bereavement; RELIGION / Christian Life / Spiritual Growth